Fe2S: The Most Fe‐Rich Iron Sulfide at the Earth's Inner Core Pressures. Issue 21 (14th November 2019) - Tateno, Shigehiko; Ozawa, Haruka; Hirose, Kei; Suzuki, Toshihiro; I‐Kawaguchi, Saori; Hirao, Naohisa
Abstract: We examined the phase relation of Fe2 S to 306 GPa and 3, 000 K and found that Fe2 S forms an orthorhombic structure with space group Pnma above 190 GPa. Reexamination of previous X‐ray diffraction data demonstrated that hexagonal close‐packed Fe coexists with Pnma Fe2 S at >2, 700 K and 290 GPa, while it concurs with CsCl (B2)‐type stoichiometric FeS at lower temperatures. Our results indicate that Fe2 S is the most Fe‐rich iron sulfide above 250 GPa where Fe3 S is not stable. It is most likely that eutectic melting occurs between Fe and Fe2 S at 330 GPa corresponding to inner core boundary conditions, instead of between Fe and Fe3 S below 250 GPa. The compression curve of Fe2 S obtained to 294 GPa shows that it is not dense enough to account for the inner core density, suggesting that the Fe‐Fe2 S eutectic liquid gives the maximum sulfur concentration in the outer core. Plain Language Summary: The chemistry of the Earth's core has long remained enigmatic; the observed density and velocity profiles indicate that the core includes some light alloying elements. The present study focuses on sulfur, one of the major candidates, and experimentally investigates the phase relations in the Fe‐FeS system under high pressures relevant to the core. The main finding of this work is that 1) Fe2 S adopts the orthorhombic Pnma structure above 190 GPa and 2) it is the most iron‐rich sulfide at >250 GPa where Fe3 S decomposes. Our data also show that Fe2 S is much lighter than the observed inner core density, suggesting that sulfur concentration in the liquid core is not high enough to crystallize Fe2 S. Key Points: Fe2 S undergoes a phase transition to the orthorhombic Pnma phase above 190 GPa Fe and Fe2 S form a eutectic system above 250 GPa, where Fe3 S is not stable Pnma Fe2 S is not dense enough to account for the inner core density